PELUANG TERJADINYA PENGANGGURAN DI PROVINSI BENGKULU : SEBERAPA BESAR? - Lisa Marini; Novi Tri Putri (Convergence: The Journal of Economic Development, 2019)
The aim of this research is to analyze how are opportunity occured unemployment based on characteristics of populations in Bengkulu province. Characteristics of populations that used are education, training/course certificate, age, gender, work experience, marital status, status in the family, and area of residence. The analytical method used to achieve this goal is the logistic regression analysis. Type of key data use row data derived from the National Labor Force Survey (Sakernas) February 2018. The result of the calculation using the program SPSS 20.0 was found that not all the variables of population characteristics significantly affect the chances of unemployment with a confidence level of 95 percent. Education and age are significantly affect of unemployment in Bengkulu Province, while training/course certificate, gender, work experience, marital status, status in the family and area residence are not significantly affect of unemployment in Bengkulu Province. Keywords: Logistic Regression Analysis, National Labor Force Survey  (Sakernas), Unemployment.